Dampak Pelaksanaan Program Nasional Pemberdayaan Masyarakat (PNPM) Mandiri Terhadap Peningkatan Pendapatan Masyarakat Miskin Desa Tompo Bulu Kecamatan Rumbia Kabupaten Jeneponto - Juhasdi Susono (Jurnal Ilmiah Al-Tsarwah : ilmu ekonomi dan keuangan (konvensional dan syariah), 2018)
The problem of this research is how the effect of revolving fund loans by the Mandiri National Community Empowerment Program (PNPM) on the income of the poor in Tompobulu Village, Rumbia Subdistrict, Jeneponto District. Rumbia District, Jeneponto Regency. This research is descriptive quantitative research with a sample design of this study amounting to 30 poor households. The research method used is simple regression analysis. The results obtained are revolving fund loans that have a positive and significant effect on increasing the incomes of the poor in Tompobulu Village, Rumbia District, Jeneponto Regency. It means that loans and loans given to the poor can increase the income of the poor in Tompobulu Village, Rumbia District, Jeneponto Regency